O efeito da deliberação CVM n.º 732 sobre os indicadores econômico-financeiros das empresas distribuidoras de energia elétrica - Amorim, Iracy Martins de (Universidade do Vale do Rio dos Sinos, 2017)
In 2010, with the adoption of International Financial Reporting Standards (IFRS), the Accounting Pronouncements Committee (CPC 00), which focuses on the Conceptual Framework for Preparation of Financial Accounting and Reporting, has changed the recognition of regulatory assets and liabilities, rights and obligations that energy distributors obtain when there is a difference between the budgeted costs and the actually spent over the period. The main change was the non-recognition of regulatory assets and liabilities in the Financial Statements for the period between 2009 and 2013. In this context, in order to reduce relevant uncertainties regarding recognition and realization or settlement, CVM Resolution No. 732/14 was approved, which authorized the accounting of these assets and liabilities. Therefore, this academic research aims to verify the effects of CVM Resolution No. 732/14 on the economic-financial indicators of electricity distributors in the period from 2008 to 2015. For the study, 63 electricity distributors were selected, but Only 49 – which have published all the financial statements and explanatory notes in the analyzed period – were studied. Then, twelve economic-financial indicators were calculated using the mean difference test as method of analysis. Results suggest that there were significant changes in the economic and financial indicators of electricity distributors in the periods from 2009 to 2013 after IFRS and from 2014 to 2015 after deliberation.
Keywords: Ativo e passivo regulatório; Deliberação n.º CVM 732/14; Indicadores econômicos financeiros; Regulatory assets and liabilities; Resolution no.CVM 732/14; Financial economic indicators; ACCNPQ::Ciências Sociais Aplicadas::Ciências Contábeis